Sageretia liuzhouensis (Rhamnaceae), a new species from Guangxi, China - Yang, Yi; Zhang, Jian-Wen; Sun, Lu; Sun, Hang (Phytotaxa, 2017)
Sageretia liuzhouensis, a new species discovered in Guangxi Zhuang Autonomous Region, China, is described and illustrated. This species was found growing in sparse forests or thickets on the top of towering limestone hills with sunny, dry habitats. It is very similar to S. camelliifolia in morphology but differs with pubescent inflorescence rachises and charcoal-gray branches, as well as smaller leaves and shorter petioles. The delimitation of this new species is also supported by phylogenetic analyses based on five DNA loci (ITS, ETS, trnL-trnF, psbA-trnH and petA-psbJ). S. camelliifolia is within a clade separated from the new species and S. thea is more closely related to S. subcaudata and S. rugosa than the new species.